Evaluasi Sifat Fisik Dan Uji Iritasi Sediaan Sabun Wajah Ekstrak Etanol Biji Salak Pondoh (Salacca zalacca (Gaert.) Voss) - Rani Prabandari; Rafi Firman Khaqiqi; Desy Nawangsari (Jurnal Farmasi & Sains Indonesia, 2022)
One of the beneficial parts in salak pondoh is the seeds. Salak pondoh seeds have antioxidant activity that can counteract free radicals. This potential can be utilized in the formulation of facial cleansing cosmetics. The purpose of this study was to formulate the ethanolic extract of salak pondoh seeds into a facial soap, then tested the physical properties and tested for acute irritation. The ethanol extract of salak pondoh seeds was formulated in several concentrations, namely 1%, 3% and 5%. Evaluation of the physical properties includes organoleptic tests, pH tests, foaming tests, viscosity tests and spreadability tests. The acute dermal irritation test used a rabbit. The data obtained were statistically tested using the one-way ANOVA method to determine the difference between each formula. The results is a brown liquid facial soap (with extract) and white (without extract). Evaluation of the physical properties resulted pH and foaming tests according to standards but viscosity and spreadability did not match. The non-fulfillment of the viscosity standards and the spreadability caused by the Viscosity Modifier (NaCl) in the formula needs to be adjusted further. This facial soap is moderately irritant to animal skin. The irritation is thought to occur because Sodium Lauryl Sulfate (SLS) in the formula can affect erythema and edema in the test animals. Keywords: salak pondoh seeds, facial soap, physical properties, irritation test